Water based scintillator ink for printed X-ray radiation detectors. (August 2018) - Oliveira, J.; Martins, P.M.; Correia, V.; Hilliou, L.; Petrovykh, D.; Lanceros-Mendez, S.
Abstract: Environmentally-friendly materials are being pursued world-wide for applications across a wide range of technologies. For application in spray-printed radiation detectors, water-based scintillator inks have been produced by combining a thermoplastic elastomer poly (vinyl) alcohol (PVA) and Gd2 O3 :Eu 3+ scintillator nanoparticles. Formulations of these green inks with different concentrations of scintillator nanoparticles have been assessed in terms of their rheological properties: the optimal concentration of scintillator nanoparticles in the water-based ink for spray-printing was 0.75 wt%. This optimized ink formulation exhibits Newtonian behavior with a viscosity around 100 cps and performance characteristics suitable for spray-printing scintillators for indirect X-ray detectors. Highlights: Environmentally-friendly scintillator inks have been developed. The inks can be applied for X-ray radiation detector development. The inks are based on poly (vinyl) alcohol and Gd2 O3 :Eu 3+ scintillator nanoparticles. The optimized ink has been applied by spray-printing to develop functional devices.